Effect of a 5A Model-based Self-management Program on Self-management Ability and Dyspnea Severity in the Elderly with Chronic Heart Failure: A Randomized Clinical Trial - Darya Shojaee; Farahnaz Mohammadi Shahboulaghi; Masoud Fallahi-Khoshknab; Mohsen Vahedi; Afsaneh Bakhtiari; Soheila Zabolypour (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives Heart failure is one of the common chronic diseases in old age and is considered as a progressive and debilitating disorder. Nowadays, the use of supportive and non-pharmacological methods in disease management and empowerment of elderly patients is of increasing importance. This study was aims to assess the effect of a 5A model-based self-management program on self-management ability and dyspnea severity in the elderly with chronic heart failure. Methods & Materials This is a randomized controlled clinical trial that was conducted on 75 eligible elderly people with heart failure (Class II or III) in Babol, Iran. They were randomly divided into two groups of intervention and control. The intervention group received the self-management training program based on the 5A model for 12 weeks. The control group received the usual training. The data before and immediately after the intervention were collected using the self-management ability scale (SMAS) and the five-item modified Medical Research Council (MMRC) dyspnea scale. The collected data was analyzed in SPSS software version 24.  Results The mean age of patients was 68.026±3.956 in the intervention group and 69.595±4.079 in the control group. There were no statistically significant differences between the two groups in terms of demographic and clinical characteristics. After the intervention, the total SMAS score and severity of dyspnea in the intervention group were significantly higher than in the control group (P<0.001). The difference was also significant in all subscales of SMAS between the two groups (P<0.001).  Conclusion Considering the positive effect of the 5A model-based self-management program on improving self-management ability and reducing the severity of dyspnea in the elderly with chronic heart failure, it can be used as a simple, low-cost, effective method, without the need to go to medical centers, to improve the quality of life of these patients.